MEMBANGUN PERADABAN PENDIDIKAN BERDASARKAN BUDAYA PANCASILA DI KABUPATEN KEPULAUAN ARU SEBAGAI BERANDA TERDEPAN NKRI MENYAMBUT INDUSTRI 4.0 - Wattimena, Rovsky Asyer (Faculty of Law, Universitas Pattimura, 2020)
At the beginning of the development of civilization in the world, there were many transitions and changes in the ways in which civilization was realized. Among them are transactions of cultural values from one area to another, exchange of information, and the latest technological discoveries. So the current phenomenon is that the understanding of the general public, especially the student generation, has begun to forget the Pancasila culture. so that one way to be able to compete and succeed in sustainable development in this era of industrial revolution 4.0 is through education. Where there is a need for a renewal of re-planting the values and culture of Pancasila at every level of education from elementary school to college. As stated in Law Number 20 of 2003 concerning the National Education System, especially the explanation of Article 37 paragraph (1) that education is intended to shape students into human beings of faith, caution and good character so that it can give a new color to the national education system. about the values of Pancasila which should be actualized in the development of national education.